Assessment of Quality of Life and Severity of Itching Pre and Post Doxepin Therapy in Dialysis Patients with Pruritus - Kousalya Prabahar, Danda Anusha, Soundararajan Periasamy, Boddu Sri Venkata Rishitha, Anand Ramanathan, Dasari Anudeep (Journal of Applied Pharmaceutical Science, 2017)
Objective: Chronic kidney disease (CKD)-associated pruritus is a significant clinical symptom affecting more than 50% of patients on hemodialysis. The main aim of this study was to assess the effects of doxepin treatment on the quality of life of pruritic patients. Material and methods: This prospective-interventional study was carried out for a period of 6 months in dialysis unit of Department of Nephrology in a tertiary care teaching hospital, Chennai. Both inpatients and outpatients of both sexes ≥ 18 years on hemodialysis or peritoneal dialysis for more than 3 months with pruritus were included for the study. A total number of 39 dialysis patients with pruritus were recruited for the study. Patients were evaluated at the beginning of the study and at the end of 2 weeks of each study period. The severity, duration, degree, direction, disability and distribution of itch were evaluated using 5D- pruritus scale. The quality of life of patients was assessed using DLQI questionnaire (Dermatology Life Quality Index). Results: There was an improvement in quality of life of patients with pruritus after doxepin therapy. Conclusion: Doxepin is a better therapy for itching and improving the quality of life in dialysis patients. Clinicians should enquire about skin irritation and itching during consultations since patients may be reluctant to admit to these symptoms due to embarrassment.
Keywords: Itch, pruritus, doxepin.